THE IMPACT OF COMPUTER ANXIETY, PERSONAL INNOVATIVENESS IN INFORMATION TECHNOLOGY, AND COMPUTER EXPERIENCE ON COMPUTER SELF-EFFICACY - Bentarani Suwardi; Zaki Baridwan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to analyze the relationship between computer anxiety, personal innovativeness in information technology, and computer experience on computer self-efficacy as well as the relation between personal innovativeness in information technology and computer experience with computer anxiety, and the level of computer anxiety based on gender for accounting students. The research is in the domain of information technology and humanistic viewpoint on personality traits based on social cognitive theory.It is quantitative research using primary data from 116 respondents of accounting students with 71% female. The survey questionnaires are distributed to 302 students of accounting directly at the end of the class, which are collected for one month.The results of the research data and hypothesis testing using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) and Social Science Statistical Package (SPSS) shows that computer anxiety (ANX) has direct negative effect to computer self-efficacy (CSE), personal innovativeness in information technology (PIT) has direct positive effect to computer self-efficacy (CSE), and personal innovativeness in information technology (PIT) and computer experience (CEX) has direct negative effect to computer anxiety (ANX), and computer anxiety (ANX) average level of female is higher than that of male.